PENGARUH MUTU PELAYANAN TERHADAP TINGKAT KEPUASAN PASIEN (Studi Kasus Puskesmas Kecamatan Pragaan Sumenep Jawa Timur) - M. Syarif; Budi Wahono; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACKThis study aims to determine and analyze which among the variables ofresponsiveness, reliability, assurance, empathy and direct evidence thatpredominantly affect the level of patient satisfaction in Puskesmas Sub DistrictPragaan Sumenep regency. Type of method used in this research is surveymethod. This method means that this study takes samples from the population anduses questionnaires (questionnaires) as the main data collection instrument. Inaddition, also conducted in-depth interviews to complete the data needed. Basedon the results of research can be concluded that the responsiveness affects patientsatisfaction, Based on the results of research that the reliability affect patientsatisfaction, Based on the results of research note that the variable assuranceaffect patient satisfaction, Based on the results known that the variable empathyaffect patient satisfaction and That the variable of direct evidence have an effecton to patient satisfaction.Keywords: Quality of Service, Guarantees and Patient Satisfaction